Mechanics of hydraulic fracturing : experiment, model, and monitoring - Zhang, Xi (Geologist) (John Wiley & Sons, Inc., 2023)
"Comprehensive single-volume reference work providing an overview of experimental results and predictive methods for hydraulic fracture growth in rocks Mechanics of Hydraulic Fracturing provides a summary of the research in mechanics of hydraulic fractures undertaken the past two decades, plus new research trends to look for in the future. The book covers the contributions from theory, modeling, and experimentation, including the applications of models to reservoir stimulation, mining preconditioning, and the formation of geological structures. The four well-qualified editors emphasize the variety of diverse methods and tools in hydraulic fracturing and help the reader understand hydraulic fracture mechanics in complex geological situations. To aid in reader comprehension, case studies on the applications of new understandings and methods are included throughout the book. Sample topics covered in the book include: Prediction of fracture shapes, sizes, and distributions in sedimentary basins, plus their importance in petroleum industry Real-time monitoring methods, such as micro-seismicity and trace tracking How to uncover geometries of fractures like dikes and veins Fracture growth of individual foundations and applications of the process Researchers and university students working in the field of fluid-driven fracture growth will find immense value in this book as a comprehensive reference on hydraulic fracturing mechanics"--